(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Familistic competence, the ability to maintain healthy family relationships and effectively manage family responsibilities, is a crucial aspect of personal development for students. This article explores the formation of familistic competence in students, focusing on the role of education, family environment, and social factors. Drawing on psychological and sociological theories, as well as empirical research, the article highlights strategies for promoting familistic competence in educational settings. It also discusses the importance of familistic competence in enhancing student well-being and academic success.